The influence of genetic manipulation of cytosolic aldolase (ALDc) on respiration in sugarcane - Scheepers, Ilana (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2005.